2018
DOI: 10.1111/jcmm.13662
|View full text |Cite
|
Sign up to set email alerts
|

MUC1‐C drives myeloid leukaemogenesis and resistance to treatment by a survivin‐mediated mechanism

Abstract: Acute myeloid leukaemia (AML) is an aggressive haematological malignancy with an unmet need for improved therapies. Responses to standard cytotoxic therapy in AML are often transient because of the emergence of chemotherapy‐resistant disease. The MUC1‐C oncoprotein governs critical pathways of tumorigenesis, including self‐renewal and survival, and is aberrantly expressed in AML blasts and leukaemia stem cells (LSCs). However, a role for MUC1‐C in linking leukaemogenesis and resistance to treatment has not bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…Similarly, these transmembrane mucins have previously been considered clinically relevant proteins that are aberrantly overexpressed in lung carcinogenesis [155]. In fact, Muc1 is a target in several preclinical and clinical trials for cancer treatment [156,157]. Concurrently, there is evidence that galectin 3 is a promising target for IPF [158] because it has a profibrotic action [159] that is partly mediated by binding to Muc1 [160].…”
Section: Principal Fibrogenic Molecules and Signal Transduction Pamentioning
confidence: 99%
“…Similarly, these transmembrane mucins have previously been considered clinically relevant proteins that are aberrantly overexpressed in lung carcinogenesis [155]. In fact, Muc1 is a target in several preclinical and clinical trials for cancer treatment [156,157]. Concurrently, there is evidence that galectin 3 is a promising target for IPF [158] because it has a profibrotic action [159] that is partly mediated by binding to Muc1 [160].…”
Section: Principal Fibrogenic Molecules and Signal Transduction Pamentioning
confidence: 99%
“…Potential new targets for therapy are directed toward inhibition of interleukin (IL)-3R activation in a subset of patients with mutant FLT3, 34,35 blocking STAT3 (epidermal growth factor receptor (EGFR) and IL-6) signaling pathways 36 and targeting MUC-1 to induce differentiation and increase survival. 37 It remains to be seen whether a subset of AML patients may benefit as much as other myeloid leukemia patients. It is quite likely that, as in the case of AML, identification of maturation arrest mutations or translocations in other cancers will be identified and appropriate blocking agents and effective treatments developed, for example, blocking pathways known to maintain stemness, such as Wnt, Oct-4, Notch, BMP, JAK, and others.…”
Section: Myeloid Leukemiamentioning
confidence: 99%
“…Other molecular signaling that has been involved in acute myeloid leukemia resistance is the expression of MUC1 (MUC1-C), an oncoprotein critical for the onset of tumorigenesis, which is overexpressed in acute myeloid leukemia blasts and leukemia stem cells. It has been demonstrated that targeting MUC1-C reduced BIRC5 levels and increased sensitivity to cytarabine, indicating that BIRC5 is involved in multiple signaling pathways required for survival in leukemia cells (Stroopinsky et al, 2018). Acute lymphoblastic leukemia (ALL) patients also presented elevated levels of BIRC5 and VEGF, especially prior to treatment with an association of idarubicin, cytosine arabinoside and etoposide.…”
Section: Leukemiamentioning
confidence: 99%